2021
DOI: 10.22449/0233-7584-2021-1-41-56
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Vertical Variability of Currents Energy in the Sub-Mesoscale Range on the Black Sea Shelf and in its Central Part

Abstract: Purpose. The study is aimed at investigating seasonal variability and vertical distribution of the submesoscale currents energy (scales L = 1 ... 10 km, T = 1 ... 10 days) in the deep and shelf zones of the Black Sea. Methods and Results. The study is based on the spectral analysis of the results obtained from the NEMO model numerical calculations performed with high spatial resolution 1 km. The analysis shows that in the areas under investigation, seasonal variability of the sub-mesoscale currents energy is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Our analysis indicates that the rise of BCI, in this case, is related to the growth of the mixed layer in the Black Sea in agreement with recent study of Puzina et al. (2021). The instability of the upper mixed layer caused by the impact of heterogeneous wind and convective mixing is the probable reason for the intense generation of SE in winter (see Callies et al., 2015).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our analysis indicates that the rise of BCI, in this case, is related to the growth of the mixed layer in the Black Sea in agreement with recent study of Puzina et al. (2021). The instability of the upper mixed layer caused by the impact of heterogeneous wind and convective mixing is the probable reason for the intense generation of SE in winter (see Callies et al., 2015).…”
Section: Resultssupporting
confidence: 93%
“…Submesoscale dynamics is characterized by significant seasonal and interannual variability (Buckingham et al., 2016; Callies et al., 2015; Capet et al., 2008; Puzina et al., 2021). Several authors showed that in many regions of the World, including the Black Sea (Puzina et al., 2021) it intensifies in winter due to the baroclinic instability of the deep winter mixed layer (Callies et al., 2015; Capet et al., 2008; Mensa et al., 2013; Puzina et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A suitable testbed for SME investigation is the Black Sea thanks to its well-developed observational and theoretical scientific facilities [4,5]. Various SME studies are performed for the Black Sea using satellite data [6][7][8] and numerical simulations [9][10][11]. They show, particularly, that SMEs can significantly impact coastal material transport [5,12] and vertical and horizontal distribution of bio-optical characteristics in the basin [13].…”
Section: Introductionmentioning
confidence: 99%